Synthesis and characterization of hydroxyapatite from waste materials / Nor Adzliana Sajahan - Nor Adzliana , Sajahan (2017)
Due to resemblance of mineral components of bones and human hard tissue, hydroxyapatite, HA with chemical formula Ca10(PO4)6(OH)2 has been widely used in medical field especially as bone replacement. All the waste materials such as chicken eggshells (CHA), duck eggshells (DHA) and cockle shells (SHA) are mainly composed of calcium carbonate, CaCO3. In this study, HA was fabricated from CaCO3 of the waste materials and diammonium hydrogen solution via microwave irradiation technique. Under the effect of microwave irradiation for 15 min, HA was produced directly in the solution and involved in crystallographic transformation. X-ray diffraction, XRD pattern revealed that no impurities other than HA was produced and the peaks were complement with standard HA (JCPDS file- 00-024-0033). All HA characteristics were evident in Fourier Transform Infra-Red, FTIR spectrum such as chemical groups of PO43-, OH- and a weak spectra of CO32-. As microwave power increased from 550W to 900W, Field Emission Scanning Electron Microscopy, FESEM micrographs showed a transition of HA particles shape from needle-like to mixture of needle-like and spherical to spherical shape. Energy Dispersive X-ray, EDX results showed that non-stoichiometric HA was produced for all samples except for SHA900 where the Ca/P ratio is 1.66 under microwave irradiation of 900W. CHA and DHA samples showed an abundance of Ca with a decreasing Ca/P ratio while Ca/P ratio of SHA increased as the microwave power increased (550-900W). Compression test showed a decreasing trend in compressive strength as the microwave power increased for all types of samples. CHA550 has the highest value of compressive strength (71.61 MPa) under the irradiation of 550W. In conclusion, the production of HA powder is reproducible, fast and environmentally friendly. The optimum microwave power to fabricate non-stoichiometric HA was 550W and 700W.